Classification of regions according to the dominant innovation barriers: The characteristics and stability of region types in Germany - Tobias Johannes Hertrich; Thomas Brenner (Regional Science Policy & Practice, 2023)
Lagging regions differ in their characteristics, implying a need for tailor-made policy measures to improve the economic situation in these regions. However, while there are differences between these regions, certain types of regions might exist that share the same obstacles to innovations, allowing for taking similar political measures. This paper examines whether such types of regions can be identified in Germany, what characteristics they possess, and how they change. For this purpose, regional characteristics that are related to innovation barriers are identified and operationalized. Then, a cluster analysis is conducted for the German labor market area. While the identified types of regions are in some way or another also discussed in the literature, the paper provides for the first time a classification within one empirical framework and allows for the study of the dynamics of the types of regions as well as the dynamics within each region inside this framework. The correspondence with the existing knowledge about German regions confirms that it is possible to do such a classification using quantitative data. Furthermore, the stability of the types of regions confirms that such a classification can be considered a good basis for policy measures. The results also depict trends that might lead to problems in the future and require policy attention.
Keywords: 320; classification of regions; cluster analysis; innovation barriers; lagging regions